Peningkatan Motivasi Belajar Melalui Model Pembelajaran Kooperatif Tipe STAD Dalam Pendidikan Agama Kristen - Irma Nelyani; Arestu Yulanda (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the improvement of learning motivation through the STAD cooperative learning model in Christian Religious Education. This study used a qualitative descriptive approach gathered from various secondary data. The findings indicate that the application of the STAD cooperative learning model in Christian Religious Education (PCE) learning has significant potential to improve student motivation and learning outcomes. This model not only helps students master cognitive knowledge but also shapes Christian character through constructive interactions, a collaborative learning environment, and rewards for individual effort and improvement. Learning becomes more lively, meaningful, and impacts students’ faith growth and academic development.